Expert opinion on advanced techniques for hemostasis in liver surgery. Issue 10 (October 2016) - Manas, D.M.; Figueras, J.; Azoulay, D.; Garcia Valdecasas, J.C.; French, J.; Dixon, E.; O'Rourke, N.; Grovale, N.; Mazzaferro, V.
Abstract: Background: Reduction of perioperative blood loss and intraoperative transfusion are two major factors associated with improving outcomes in liver surgery. There is currently no consensus as to the best technique to achieve this. Methods: An international Panel of Experts (EP), made up of hepatobiliary surgeons from well-known high-volume centres was assembled to share their experience with regard to the management of blood loss during liver resection surgery. The process included: a review of the current literature by the panel, a face-to-face meeting and an on-line survey completed by the EP prior to and following the face-to-face meeting, based on predetermined case scenarios. During the meeting the most frequently researched surgical techniques were appraised by the EP in terms of intraoperative blood loss. Results: All EP members agreed that high quality research on the subject was lacking. Following an agreed risk stratification algorithm, the EP concurred with the existing research that a haemostatic device should always be used along with any user preferred surgical instrumentation in both open and laparoscopic liver resection procedures, independently from stratification of bleeding risk. The combined use of Ultrasonic Dissector (UD) and saline-coupled bipolar sealing device (Aquamantys ® ) was the EP preferred technique for both open and laparoscopic surgery. Conclusions: This EP propose the use of a bipolar sealer and UD for the best resection technique and essential equipment to minimise blood loss during liver surgery, stratified according to transfusion risk, in both open and laparoscopic liver resection.